An elastoplastic model for cohesionless soils under a wide range of confining pressures - Linlong Mu; Shunwei Wang; Xiaoxiang Chen; Yimin Lu (European Journal of Environmental and Civil Engineering, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

An ultrasound-driven bioengine for apoptosis inhibition and immune homeostasis regulation in intervertebral disc degeneration - Dengbo Yao; Linlong Li; Yu Tang; Juntao Yao; Hang Liu; Jie Weng; Yu Wang; Qingquan Kong; Huan Tan (Chemical Engineering Journal, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Enhanced puncture event detection for teleoperated needle insertion robotic system - Hongbing Li; Yubin Lan; Yuling Li; Linlong Li; Rui Wang (Medical & Biological Engineering & Computing, 2026)

N, S-co-doped carbon quantum dots as a versatile platform for monitoring hydrogen sulfide and nitrite based on Fe2+/Fe3+ redox cycle: Applications in food safety and bioimaging - Yaping Zhong; Kayi Shao; Ruixia Zhang; Linlong Zhang; Dong Wang (Food Control, 2026)

Experimental study on pitch motion mitigation of a 15 MW spar wind turbine using passive gyro stabilizers - Junlei Wang; Haoran Li; Jisheng Zhang; Dawei Guan; Linlong Tong; Hao Chen; Xiaoqiang Kou (Ocean Engineering, 2026)

Experimental study of hydrodynamics and soil responses around a sandbar and their effects on bed-level evolution - Mengyan Luo; Linlong Tong; Jisheng Zhang; Yakun Guo; Hao Wang; Ning Chen (Ocean Engineering, 2026)

Reducing local scour around monopiles using arc-shaped sacrificial piles under unidirectional flow - Hao Chen; Jisheng Zhang; Hao Hu; Linlong Tong; Yiming Ji; Haoran Li; Yanhong Wang (Ocean Engineering, 2026)

Contrasting trajectories of crustacean stocks in coastal China: impacts of fishing intensification vs. enhancement initiatives - Linlong Wang; Guoqing Zhao (Hydrobiologia, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Pore pressure responses and seepage flow inside an unsaturated seabed caused by a floating cylinder - Linlong Tong; Yiming Ji; Jisheng Zhang; Hao Chen; Liangcai Wang; Shoupeng Xie; Yakun Guo (Ocean Engineering, 2026)

Ultimate soil resistance analysis of horizontally loaded piles in c-φ soils: a modified p-y curve formulation - Linlong Mu; Shunwei Wang; Xiaoxiang Chen; Jiawei Zhang; Guangming Yu (Ocean Engineering, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Long-term effects of environmental changes on taxonomic, functional, and phylogenetic alpha and beta diversity of fish communities in the Minjiang Estuary - Pengzhan Zhang; Yuru Li; Xin Peng; Linlong Wang; Yefu Kong; Hao Tian; Bin Kang (Environmental Biology of Fishes, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

MoS2 QDs-decorated mesoporous polydopamine nanoparticle as a GSH responsive peroxidase-like nanozyme for effective antibacterial therapy - Kayi Shao; Linlong Zhang; Yaping Zhong; Dong Wang (Chemical Engineering Journal, 2025)

Statistical characteristics of turbulence in combined wave-current boundary layer flows - Xuan Zhang; Jinhai Zheng; Chi Zhang; Jisheng Zhang; Yakun Guo; Linlong Tong; Rupeng Wang; Haoran Li (Ocean Engineering, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Core-sheath structured CNT@Ni-CNT fiber-based multifunctional fabric with high-sensitivity, wide-range strain sensing, and enhanced electromagnetic shielding absorption - Yiqian Shao; Lihua Zou; Yang Chen; Lirui Wang; Linlong Song; Hang Xu; Ping-an Yang (Chemical Engineering Journal, 2025)

Multiple environmental factors drive the functional dimension of fish communities in the Central East China Sea - Pengzhan Zhang; Yang Liu; Yang Yan; Linlong Wang; Yefu Kong; Xin Peng; Bin Kang (Marine Environmental Research, 2025)

A Novel Coumarin Based Fluorescent Probe for Cu²⁺ Detection as well as Applications - Yunke Gao; Linlong Deng; Lei Xue; Yihan Cheng; Shuai Fu; Haibin Wang (Journal of Fluorescence, 2025)

Using alpha, beta, and zeta diversity to map the structure and function of fish community in the central East China Sea - Pengzhan Zhang; Yefu Kong; Linlong Wang; Xin Peng; Bin Kang (Hydrobiologia, 2025)

A model fusion method based DAT-DenseNet for classification and diagnosis of aortic dissection - Linlong He; Shuhuan Wang; Ruibo Liu; Tienan Zhou; He Ma; Xiaozeng Wang (Physical and Engineering Sciences in Medicine, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Trophic niche partitioning of golden cuttlefish (Sepia esculenta) during ontogeny revealed by stable isotope analysis and DNA metabarcoding - Zhang Yuyang; Wang Linlong; Sun Xin; Dong Jianyu; Zhan Qipeng; Zhang Xiumei (Fisheries Research, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

Transcriptional regulation and alternative splicing reveal the molecular strategies of Bombay duck Harpadon nehereus to hypoxia - Zhicheng Sun; Linlong Wang; Yefu Kong; Jiachen Sun; Bin Kang (Fisheries Science, 2024)

The Impact of Pre-Existing Faults on Fault Geometry during Multiphase Rifts: The Jiyang Depression, Eastern China - Di Wang; Linlong Yang; Wei Li; Xidong Wang (Journal of Marine Science and Engineering, 2023)
The combination of multi-phase extension and pre-existing fault reactivation results in a complex fault pattern within hydrocarbon-bearing basins, affecting hydrocarbon exploration at different stages. We used high-resolution 3D seismic data and well data to reveal the impact of multi-phase extension and pre-existing fault reactivation on Cenozoic fault pattern changes over time in the Jiyang Depression of eastern China. The results show that during the Paleocene, a portion of NW-striking pre-existing faults reactivated under NS extension and controlled the basin structure (type 1). Other parts of the NW-striking pre-existing faults stopped activity and served as weak surfaces, and a series of NNE-striking faults were distributed in an en-echelon pattern along the NW direction at shallow depths (type 2). In areas unaffected by pre-existing faults, NE-striking faults formed perpendicular to regional stresses. During the Eocene, the regional stresses shifted clockwise to near-NS extension, and many EW-striking faults developed within the basin. The NE-striking faults and the EW-striking faults were hard-linked, forming the ENE-striking curved faults that controlled the structure in the basin (type 3). The NNE-striking faults were distinctly strike-slip at this time, with the ENE-striking faults forming a horsetail pattern at their tails. Many ENE-striking faults perpendicular to the extension direction were formed in areas where the basement was more stable and pre-existing faults were not developed (type 4). There were also developing NS-striking faults that were small in scale and appeared in positions overlapping different main faults (type 5). Additionally, different fault patterns can guide different phases of hydrocarbon exploration. Type 1, type 2, and type 3 faults are particularly suitable for early-stage exploration. In contrast, type 4 and type 5 faults are more appropriate for mature exploration areas, where they may reveal smaller hydrocarbon reservoirs.

Three-dimensional finite element analysis for uplifting independent helix plate anchor in uniform clay - Yunhan Huang; Linlong Mu; Peipei Wang (Ocean Engineering, 2023)

Renewable ultrathin carbon nitride nanosheets and its practical utilization for photocatalytic decarboxylation free radical coupling reaction - Qing Xu; Linlong Dai; Zijie Wang; Jiaqi Wu; Hongyan Lu; Lutong Yuan; Qiaohong Zhu; Xiaofei Zeng (Chemical Engineering Journal, 2023)

Fish growth evaluation and fishery dynamic assessment of Harpadon nehereus providing insights for its population expansion in the Northern East China Sea - Linlong Wang; Jintao Li; Bin Kang (Hydrobiologia, 2022)

Root-associated microbiota drive phytoremediation strategies to lead of Sonchus Asper (L.) Hill as revealed by intercropping-induced modifications of the rhizosphere microbiome - Xinyue Mei; Ying Wang; Zuran Li; Marie Larousse; Arthur Pere; Martine da Rocha; Fangdong Zhan; Yongmei He; Linlong Pu; Franck Panabières; Yanqun Zu (Environmental Science and Pollution Research, 2022)
Intercropping or assistant endophytes promote phytoremediation capacities of hyperaccumulators and enhance their tolerance to heavy metal (HM) stress. Findings from a previous study showed that intercropping the hyperaccumulator Sonchus asper (L.) Hill grown in HM-contaminated soils with maize improved the remediating properties and indicated an excluder-to-hyperaccumulator switched mode of action towards lead. In the current study, RNA-Seq analysis was conducted on Sonchus roots grown under intercropping or monoculture systems to explore the molecular events underlying this shift in lead sequestering strategy. The findings showed that intercropping only slightly affects S. asper transcriptome but significantly affects expression of root-associated microbial genomes. Further, intercropping triggers significant reshaping of endophytic communities associated with a ‘root-to-shoot’ transition of lead sequestration and improved phytoremediation capacities of S. asper . These findings indicate that accumulator activities of a weed are partially attributed to the root-associated microbiota, and a complex network of plant–microbe-plant interactions shapes the phytoremediation potential of S. asper . Analysis showed that intercropping may significantly change the structure of root-associated communities resulting in novel remediation properties, thus providing a basis for improving phytoremediation practices to restore contaminated soils.

Stable Isotope Analysis Revealed Ontogenetic Changes in Trophic Ecology and Migration Patterns of Sepia esculenta in the Northern Coastal Waters of China - Linlong Wang; Yang Liu; Xiumei Zhang (Frontiers in Marine Science, 2022)
Golden cuttlefish ( Sepia esculenta ), the most economically important cephalopod in the northern coastal seas of China, had experienced greatly reduced population biomass due to continuous fishing pressure in recent decades. Understanding the trophic ecology and clarifying the spatial distribution of wintering ground can help develop management plans for this species. In this study, the ontogenetic changes in the trophic ecology of S. esculenta in the Qingdao coastal water were determined, and the migration patterns were studied using stable isotope analysis. Cluster analysis based on isotopic values divided S. esculenta with different lengths into groups: 11–20, 21–100, and 121–200 mm. A significant difference in the δ 13 C values between the groups 11–20 mm (−17.10‰) and 21–100 mm (−15.89‰) illustrates an ontogenetic change in the feeding habits. Due to the migratory habits of S. esculenta , the δ 13 C value of the group 121–200 mm (−16.39‰) was lower than that of the group 21–100 mm. The δ 15 N values of S. esculenta were found to increase in length, and there was a clear linear relationship between different S. esculenta groups, suggesting that the wintering ground may locate in the same latitude as the spawning ground (i.e., the middle Yellow Sea). Furthermore, the trophic relationship between S. esculenta and coexisting species was assessed, revealing that the group 11–20 mm of S. esculenta has some overlap of carbon isotope space with other species, suggesting that these species may feed on it as prey. Thus, slightly increasing the length to more than 20 mm may reduce the pressure of being the prey of post-release juveniles of S. esculenta and improve the effect of release.

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Fishery Dynamics, Status, and Rebuilding Based on Catch-Only Data in Coastal Waters of China - Linlong Wang; Li Lin; Yang Liu; Lu Zhai; Shen Ye (Frontiers in Marine Science, 2022)
China has become the largest contributor to marine fisheries in the world with its fishing fleets explosively increasing their fishing effort and resulting catch, but its fishery composition and sustainability have deteriorated. Limited information on fishery exploitation status encumbers effective resource management. In this study, a data-poor Monte Carlo method, the Catch-Maximum Sustainable Yield (CMSY) method, was used to estimate the historical exploited dynamics and current stock status of ten Chinese economic marine fish stocks, including Trichiurus lepturus , Larimichthys crocea , Larimichthys polyactis , Thamnaconus modestus , Scomberomorus niphonius , Ilisha elongate , Decapterus maruadsi , Scomber japonicus , Engraulis japonicus , and Clupea pallasii , which accounted for about 50% of total fish catches in the coastal waters of China and covered five functional groups (i.e., large, medium benthopelagic, large, medium, and small pelagic). Species L. crocea and L. polyactis had been subjected to overfishing since the 1950s. The others showed a decreasing trend in biomass along with the explosively increasing fishing efforts since the 1990s. Benthopelagic fish experienced overfishing pressure about a decade earlier than pelagic species. All the fish stocks investigated in this study were depleted (current biomass lower than the biomass capable of producing maximum sustainable yields, i.e., B < B msy ) in 2019, and most species were still facing high-fishing pressure (current fishing mortality higher than the mortality capable of producing maximum sustainable yields, i.e., F > F msy ). Also, a Schaefer model was used to assess stocks rebuilding status until 2030 under four exploitation scenarios, i.e., fishing mortality equals 0.5, 0.6, 0.8, or 0.95 times F msy . Most species stocks will likely recover to the B msy , which indicates that reduction of fishing pressure is probably the most effective way for fishery recovery.

Redistribution of the lizardfish Harpadon nehereus in coastal waters of China due to climate change - Linlong Wang; Zhixin Zhang; Longshan Lin; Xin Peng; Li Lin; Bin Kang (Hydrobiologia, 2021)

Characterising the nature, evolution and origin of detachment fault in central depression belt, Qiongdongnan Basin of South China Sea: evidence from seismic reflection data - Jianye Ren; Daojun Zhang; Dianjun Tong; Anmin Huang; Yahui Wang; Chao Lei; Qianmei Zuo; Yanghui Zhao; Weijun He; Linlong Yang (Acta Oceanologica Sinica, 2014)